Systematic Review of the Association between Lipoprotein - Associated Phospholipase A2 and Atherosclerosis - Liu, MD, MPH, Jing; Hong, MD, PhD, Yuling; Qi, MD, PhD, Yue; Zhao, PhD, Fan; Zhao, MD, PhD, Dong (North American Journal of Medicine and Science, 2011)
Lipoprotein-associated phospholipase A2 (Lp-PLA2) is a novel inflammatory biomarker. Basic research has shown that Lp-PLA2 is involved in the pathogenesis of atherosclerosis. In the past decade, an increasing number of epidemiological studies have investigated the association of Lp-PLA2 with atherosclerosis, but its roles in the different stages of atherosclerosis are not established. By undertaking a systematic review of the epidemiological studies on the relationship between Lp-PLA2 and atherosclerotic cardiovascular disease (CVD)/subclinical atherosclerosis, we tried to evaluate the relationship between Lp-PLA2 and the different stages of atherosclerosis. MEDLINE, Cochrane Library, and National Knowledge Infrastructure (CNKI) were searched up to September 1st, 2011. The references in all the located articles were manually searched. Epidemiological studies on the association of Lp-PLA2 with CVD and subclinical atherosclerosis, with total CVD, coronary heart disease (CHD), stroke, and subclinical atherosclerosis as their observation endpoints or outcome variables, were included in this study. Studies which did not assess the hazard ratio (HR), relative risk (RR), or odds ratio (OR) of Lp-PLA2 or which did not adjust for other known risk factors were excluded. The general information, study design, sample size, outcome variables and their definitions, follow-up duration, Lp-PLA2 measurements, variables adjusted in the multivariate analysis and main results in the literatures were retrieved. Thirty-nine studies were enrolled in this systematic review. Thirty-three studies (49, 260 subjects) investigated the relationship between Lp-PLA2 and CVD, among which 31 showed that increased Lp-PLA2 is associated to high risk for incidence or mortality of CVD: HR/RR per 1 standard deviation (SD) increase = 1.17–1.40; RR for the highest as compared with the lowest quartile was 1.41–3.75 (1.8–2.5 in most studies). Six studies (four cross-sectional studies and two case-control studies, with an overall sample size of 5,537) explored the relationship between Lp-PLA2 and subclinical atherosclerosis; among them, two studies demonstrated that Lp-PLA2 was associated with coronary artery calcification in young adults and men. In conclusion, many epidemiological studies have demonstrated that Lp-PLA2 increases the risk of clinical CVD events. However, whether there is a similar association between Lp-PLA2 and subclinical atherosclerosis remains unclear. Whether Lp-PLA2 exerts its effect during the occurrence of clinical events promoted by unstable plaques or at the early stage of atherosclerosis needs to be clarified in further prospective studies.